The Urgence of Establishing the Character of Independent Students with Achievements An-Nur Foundation, Sumberurip Village Pronojiwo Lumajang - Yuliati, Dian; Karan, Achmad Mustofa; Lestari, Dyah Mumpuni Indah Palupi Asih; Hunowu, Fairuz Darell Azariah; Farizy, Haffif Al; Darmayani, Mariel Tania; Rakhmania, Nadin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Education is one of the important factors to support one's future. Madrasas are one of the places of education that currently tend to be an option. This existence is caused by religious values ​​which are more emphasized in madrasas. In madrasa students are expected to be independent and achieve, in accordance with the slogan of the madrasa itself. Independent is meant to be able to know, recognize himself and then be able to develop himself. While the word 'achievement,' has the meaning of an effort from independence and proud performance. However, observations at the An-Nur Foundation found that further guidance was needed to shape the character of Madrasah Ibtidaiyah students who were independent achievers. This research was conducted using the Community Based Research (CBR) method, which is a research conducted with the community in solving the problems they are experiencing. The emergence of CBR begins with the development of relationships between researchers and community organizations that jointly carry out research activities using scientific methods and community-based approaches. The results of this study are in the form of a pocketbook entitled Majmu>‘a>t al-Adhka>r wa al-S}alawa>t (A Collection of Remembrance and Salawat) which is a summary of a series of madrasa activities at the An-Nur Foundation. The existence of this pocketbook is expected to be able to assist in carrying out the existing series of activities.